Caffeine supplementation improves physical performance without affecting fatigue level: a double-blind crossover study - Yuri Campos; Ángel Lago-Rodríguez; Alejandro San Juan; Victor Moreno-Pérez; Alvaro Lopez-Samanes; Antonio Sánchez-Oliver; Sandro Da Silva; Raúl Domínguez (Termedia Publishing House, 2021)
This study examined the effect of caffeine supplementation (CAFF) in a Wingate test (WT), and the behaviour of blood lactate concentrations (BLa) and neuromuscular fatigue (NMF), measured as reduced countermovement jump (CMJ) performance, in response to the WT. In a double-blind crossover study, 16 participants attended the laboratory twice, separated by a 72-hour window. In the sessions, participants first ingested 6 mg·kg-1 of either CAFF or placebo (PLAC), and then performed a WT. BLa was measured before (L-pre), and 0.5 min (L-post-0.5) and 3.5 min (L-post-3.5) after conducting the WT. The CMJ test was conducted before (CMJ pre), after (CMJ post), and 3 min after completing (CMJ post-3) the WT. The results indicated that CAFF enhanced peak power (Wpeak: + 3.22%; p = 0.040), time taken to reach Wpeak (T_Wpeak: -18.76%; p = 0.001) and mean power (Wmean: + 2.7%; p = 0.020). A higher BLa was recorded for CAFF at L-post-0.5 (+ 13.29%; p = 0.009) and L-post-3.5 (+ 10.51%; p = 0.044) compared to PLAC. CAFF improved peak power (PP; + 3.44%; p = 0.003) and mean power (MP; + 4.78%; p = 0.006) at CMJ pre, compared to PLAC, whereas PP and MP were significantly diminished at CMJ post and CMJ post-3 compared to pre ( p < 0.001 for all comparisons) under both the CAFF and PLAC conditions. PP and MP were increased at post-3 compared to post ( p < 0.001 for all comparisons) for both conditions. In conclusion, CAFF increased WT performance and BLa without affecting NMF measured by CMJ. Thus, CAFF may allow athletes to train with higher workloads and enhance the supercompensation effects after an adequate recovery period.